A mini review of the specialties of the bio-oils produced from pyrolysis of 20 different biomasses. (October 2019) - Gholizadeh, Mortaza; Hu, Xun; Liu, Qing
Abstract: Bio-oil contains organics with the potential application as liquid fuels for use in vehicles via upgrading. Nevertheless, the applications of bio-oil depend on its properties, which are further indicated by the origin of the biomass feedstock, pyrolysis conditions and configuration of pyrolysers. It of importance of establishing the correlation between the properties of biomass and features of corresponding bio-oil formed, the bio-oils obtained from 20 types of biomasses ranging from different woods, agriculture wastes including various grass types and other biomasses including coconut shell, etc were studied. The features of bio-oils were compared and correlated with the features of the biomasses. The results indicated that the relative proportions of the subcomponents of biomass had significant impacts on the distribution of the species produced. For woody biomass, cellulose and hemicellulose could have more contribution to the formation of the gas. Effects of the subcomponents in biomass on the formation of bio-oil and biochar were very complicated, and it was difficult to establish direct correlation between lignin content and char yield. Nevertheless, the inorganic species in biomass catalyzed charring reactions, leading to the biochar formation increase while the decreased production of bio-oil. Other factors such as mass transfer limitations, heat transfer and especially biological structures of biomass also influenced the products. Comparing with woody biomass, higher yields of gaseous products and biochar with correspondingly lower bio-oil yields was produced from the herbaceous biomass, relating to the high ash content and the distinct biological structure of herbaceous biomass. Graphical abstract: Image 1 Highlights: This study reviewed properties of bio-oil produced from different biomass types. Subcomponents of biomasses significantly impacted the bio-oils produced. Establishing a correlation of biomass types and bio-oil features is investigated. Extractives, inorganics and biomass structures affect bio-oil properties. Properties of bio-oil from various biomasses do not meet standard for engine fuel.